Case Management on the Front Lines of COVID-19: The Importance of the Individualized Care Plan Across Care Settings. Issue 2 (March 2021) - Baker, Michelle; Nelson, Sheila; Krsnak, Jean
Abstract : Purpose: Since the outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and the disease known as COVID-19, case management has emerged as a critical intervention in the treatment of cases, particularly for patients with severe symptoms and medical complications. In addition, case managers have been on the front lines of the response across the health care spectrum to reduce risks of contagion, including among health care workers. The purpose of this article is to discuss the case management response, highlighting the importance of individual care plans to provide access to the right care and treatment at the right time to address both the consequences of the disease and patient comorbidities. Primary Practice Settings: The COVID-19 response spans the full continuum of health and human services, including acute care, subacute care, workers' compensation (especially catastrophic case management), home health, primary care, and community-based care. Implications for Case Management Practice: From the earliest days of the pandemic, case managers have assumed an important role on the front lines of the medical response to COVID-19, ensuring that procedures are in place for managing a range of patients: those who were symptomatic but able to self-isolate and care for themselves at home; those who had serious symptoms and needed to be hospitalized; and those who were asymptomatic and needed to be educated about the importance of self-isolating. Across the care spectrum, individualized responses to the clinical and psychosocial needs of patients with COVID-19 in acute care, subacute care, home health, and other outpatient settings have been guided by the well-established case management process of screening, assessing, planning, implementing, following up, transitioning, and evaluating. In addition, professional case managers are guided by values such as advocacy, ensuring access to the right care and treatment at the right time; autonomy, respecting the right to self-determination; and justice, promoting fairness and equity in access to resources and treatment. The value of justice also addresses the sobering reality that people from racial and ethnic minority groups are at an increased risk of getting sick and dying from COVID-19. Going forward, case management will continue to play a major role in supporting patients with COVID-19, in both inpatient and outpatient settings, with telephonic follow-up and greater use of telehealth.